STUDI FENOMENA MENJEMUR PAKAIAN YANG MEMBENTUK CITRA KURANG BAIK BANGUNAN RUMAH SUSUN: Studi Kasus: Rumah Susun Sarijadi, Kota Bandung - Karya, Nurul Sucya (Jurnal Koridor, 2017)
Menjemur is literally means drying laundry by hanging them to be exposed by the sun or open air. In Indonesia, misplaced menjemur phenomenon is frequently seen in low-cost apartment, which is giving a bad image to the building. By choosing the case of low-cost apartment (Rumah Susun) in Sarijadi Bandung, this small research tried to dig deeper towards misplaced menjemur phenomenon in Rumah Susun. The data collection method used for this small research is field observation and interview to the Rumah Susun occupants, which are then being analyzed descriptively. It can be seen that the Rumah Susun occupants improperly place their laundry to be dried, such as in balconies, corridors, stairs, and windows. This thing happened because there isn't any facility to place their laundry in Rumah Susun provided. Moreover, this phenomenon shows that the occupants don't have any other choice towards their settlement, which is called "bounded choice", as the result of Rumah Susun building programme orientation which is done by top-down method that produce a nearly uniformed building form. This bounded choice phenomenon could harm the Rumah Susun image, and in long term could reduce the occupants interest to live in Rumah Susun. An occupant behaviour-based improvement towards the Rumah Susun building programme is needed in the future, to produce a Rumah Susun form which has a good image. The outcome of this research could be a material to evaluate the Rumah Susun building design.